Maternal mortality. Experience at Edgardo Rebagliati Martins National Hospital, EsSalud 1958- 2002 - Farro, Andrés (2015)
Objective: To determine maternal mortality rate tendency at a Peruvian Social Security National Hospital during the 44 years of existence. Design: Epidemiological descriptive retrospective study of maternal deaths registered at our Hospital from 1958 through 2002. Subjects: Two hundred and thirty-three women that died during pregnancy, delivery or postpartum. Setting: Department of Obstetrics and Gynecology, Edgardo Rebagliati-Martins National Hospital, EsSalud. Results: Direct obstetrical deaths represented 71,7% (167 cases) of all deaths, including 27,0% (63 cases) of pre-eclampsia-eclampsia cases, 23,2% (54 cases) infections, 14,6% (34 cases) hemorrhage and 6,9% (16 cases) other direct obstetrical causes. Indirect obstetrical causes represented 27,9% (65 cases) and non-related causes 0,4% (1 case). Maternal mortality rate was 42,61100 000 live-newborns, rate unchanged for the past 12 years but for a slight increase in indirect causes. Conclusions: We discuss the probable reasons for non-improvement in maternal mortality rate at our Hospital and emphasize on measures that may contribute to decrease maternal deaths, including obstetrical attention with quality and warmth, better reference and improvement of the hospital obstetrical equipment.